STUDI VARIASI RASIO BATUBARA KALORI RENDAH DAN BIOMASSA SEKAM PADI DALAM PEMBUATAN BIO-BRIKET BERDASARKAN ANALISIS PROKSIMAT, TOTAL SULFUR, DAN NILAI KALOR - muzakki; A. Sry Iryani (UIR Press, 2026)
This study aims to examine the effect of different mixture ratios of low-calorie coal and rice husk biomass on bio-briquette characteristics and to determine the optimum ratio as a more environmentally friendly alternative fuel. The ratio variations were 0:1, 1:0, 1:2, 2:1, 3:1, 1:3, and 2:3 (coal: rice husk). The analyzed parameters included proximate analysis, namely moisture, ash, volatile matter, and fixed carbon, as well as total sulfur and calorific value. The data were evaluated descriptively using range, mean, standard deviation, and correlation with coal fraction; one-way ANOVA can be applied when replicated data are available for each treatment. The results showed that increasing the coal fraction increased fixed carbon and calorific value, but also increased ash and total sulfur. In contrast, increasing the rice husk fraction reduced sulfur and ash, but increased moisture and volatile matter. The 3:1 ratio was selected as the most balanced ratio because it produced a calorific value of 5,800 cal/g, a sulfur content of 0.60%, and a moisture content of about 5.50%. However, because ash and volatile matter remained relatively high and fixed carbon was still low compared with certain bio-briquette standards, this optimum ratio should be further validated through actual combustion tests, including ignition time, combustion duration, flame stability, and SO₂ emission.